Modeling of Economic And Military Expenditure of South Pacific Countries to Increase the Role of Indonesian Diplomacy through the South Pacific Defense Ministers Meeting (SPDMM) Forum - Gibran, Muhammad Nur; Mahroza, Jonni; Afrizal, Afrizal; Priyanto, Priyanto; Patmi, Sri; Budiyanti, Fatwa; Sugiman, Ranon; Prakoso, Lukman Yudho (Formosa Journal of Applied Sciences, 2024)
The South Pacific is a western lake for the West, Asia and China. This is because of its strategic location, abundant natural resources but minimal human resources in managing it, so that this region becomes a contest for superpower state hegemony. The purpose of this study is to analyze the relationship of causality, response in case of shock from a variable through impulse response, long-term and short-term effects of economic growth variables, investment, foreign debt, exports, imports and military expenditure, and forecasting based on actual data up to 2045. The method used in this study is VECM / VAR. Data collection was obtained from reports from the Ministry of Defense, Ministry of Economic Affairs, literature studies and previous research.